First report of Fusarium proliferatum causing root rot in soybean (Glycine max L.) in Canada. (January 2015) - Chang, K.F.; Hwang, S.F.; Conner, R.L.; Ahmed, H.U.; Zhou, Q.; Turnbull, G.D.; Strelkov, S.E.; McLaren, D.L.; Gossen, B.D.
Abstract: Soybean plants showing symptoms of root rot were collected from fields in western Canada to determine the etiology of the disease. Four Fusarium spp., Fusarium avenaceum, Fusarium culmorum, Fusarium oxysporum and Fusarium proliferatum, were identified based on their cultural and morphological characteristics. All of the isolates of these species were pathogenic on soybean. Identification of F. proliferatum was confirmed by PCR analysis with the F. proliferatum -specific primer set CLPRO1/CLPRO2. Amplicons of the target fragments (partial calmodulin (cld) gene, 526 bp) were obtained only from DNA of isolates tentatively identified as F. proliferatum, and sequencing of the amplicon showed it shared 100% identity with the cld gene sequences of F. proliferatum in GenBank. F. proliferatum was the most aggressive of the four Fusarium species identified, causing the greatest root rot severity and reduction of seedling emergence. F. avenaceum was the second most aggressive and caused a greater reduction in seedling numbers than F. culmorum or F. oxysporum . Correlation analysis showed that seedling emergence, shoot dry weight, and seed yield decreased, and root rot severity increased, with the log of inoculum density of F. proliferatum . This is the first report of F. proliferatum causing soybean root rot in Canada. Highlights: Four Fusarium species were identified in a soybean root rot survey in western Canada. Fusarium proliferatum was the most aggressive pathogen of these species. This is the first report of F. proliferatum causing soybean root rot in Canada. Soybean growth decreased and disease increased, as F. proliferatum multiplied.